Deacetylation degree of chitosan by various bases and its metal adsorption ability related on antioxidant activity - Saleh, A.; Mukhtar, Syed Aqif; Fawwaz, M.; Pratama, M.; Kosman, R.; Naid, T. (2015)
© 2015, Journal of Chemical and Pharmaceutical Research. All Rights Reserved.Chitosan is the result of deacetylation process of chitin compounds commonly found in the outer skin of the animal groups crustaceans such as shrimp and crab. The purpose of this research is to obtain scientific data about the comparative degree of deacetylation of chitosan tiger shrimp shells using several strong bases and the ability of chitosan to adsorb ferrous metals as one method of antioxidants testing. The first stage is the produce of chitin from shrimp shells by demineralization, deproteination and depigmentation, the second phase is produce of chitosan with deacetylation used several base at a concentration of 50% (w/v). Chitosan produced from this process is analyzed degree of deacetylation with FT-IR spectrophotometer through analysis functional groups of amine and hydroxyl. Strong base that produces the best degree of deacetylation of chitosan further optimized. Chitosan obtained are then tested antioxidant activity through the ferrous metal adsorption. The amount of metal that can be adsorbed by chitosan was observed using a UV-VIS spectrophotometer. The results showed the degree of deacetylation of chitosan by using NaOH, KOH and Ca(OH)2 respectively by 52.34%, 37.89% and 42.17%. Results of the optimization degree of deacetylation by the use of NaOH 60% (w/v) of 81.94%. Metal ion adsorption test results on chitosan weight of 50 mg, 250 mg and 500 mg respectively 47.65%, 80.07% and 87.00%. It showed that chitosan is able to act as an antioxidant by adsorption of the metal ions.